Modelos de sobrevivência para estimação do período de latência do câncer - Bettim, Bárbara Beltrame (Universidade Federal de São Carlos, 2017)
Cancer is responsible for about 13% of all deaths in the world occuring mainly in people who are late diagnosed and in advanced stages. Due to its devastating characteristics and the growing prevalence of the disease, it is unquestionable the need of constant investigation and research in this area, in order to improve the early detection and to help in its prevention and treatment. Among the existing approaches, one alternative is the creation of techniques to estimate the "silent" growth period of cancer, which means to know the beginning moment of the carcinogen period, also known as latency period. In a literature review, it was found an shortage of models that estimate the latency of cancer, indicating the need of study about this theme. In this context, survival analysis methods appear as an useful tool to build these models. In this study, a review of an existing model is presented, as well as its formulation and estimation methods. Furthermore, an application on real data and a discussion of the obtained results are made. As a result, it was identified the need to formulate a new model, because of the limitations of the studied one. We present 3 alternative models that solve the points presented in the discussion, with applications.
Survival models to estimate the latency period of cancer
Keywords: Período de latência; Análise de sobrevivência; Câncer; Latency period; Survival analysis; Cancer; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA